Three-phase electrical power - Fleckenstein, Joseph E. (CRS Press, 2016)
[This book] addresses all aspects of three-phase power circuits. The book treats the transmission of electrical power from the common sources where it is generated to locations where it is consumed. At typical facilities where electrical power is used, the book covers the important topics of grounding, currents, power, demand, metering, circuit protection, motors, motor protection, power factor correction, tariffs, electrical drawings, and relays. Included in the text are the necessary methods of computing currents and power in all possible types of circuit applications as those that are balanced, unbalanced, leading, lagging, three-wire, and four-wire.